Cytokine release syndrome after allogeneic stem cell transplantation with posttransplant cyclophosphamide. Issue 4 (5th August 2020) - Solán, Laura; Landete, Elena; Bailén, Rebeca; Dorado, Nieves; Oarbeascoa, Gillen; Anguita, Javier; Díez‐Martín, Jose Luis; Kwon, Mi
Abstract: Cytokine release syndrome (CRS) is a systemic inflammatory response with aberrant immune activation and immune hyperstimulation, that leads to increased cytokine levels and inflammation. CRS has been described after antibody and cellular‐based therapies. The use of posttransplant cyclophosphamide (PTCy) as graft‐vs‐host disease (GVHD) prophylaxis in haploidentical hematopoietic stem cell transplantation (haplo‐HSCT) has led to the extension of allogeneic HSCT to patients without HLA‐identical donors. Furthermore, PTCy has also been introduced in matched and unrelated donor HSCT. However, description of incidence and clinical impact of CRS on outcomes in these patients is scarce. We retrospectively analyzed 107 consecutive haplo‐HSCT and 39 HLA‐identical HSCT with PTCy from 2010 to 2017 in our institution. We used published CRS criteria to identify 76% and 14% of patients who developed CRS after haplo‐HSCT and HLA‐identical HSCT, respectively. Most patients presented CRS grades 1 and 2. Only one patient from the whole series presented grade 3 CRS and required tocilizumab therapy. The use of peripheral blood stem cells (PBSC), as well as total nucleated cells infused were associated with an increased risk of CRS. Patients who presented CRS developed grade II‐IV acute GVHD more frequently than those who did not (60% vs 28.6% respectively, P = .012). The development of CRS was not significantly associated with nonrelapse mortality or overall survival. CRS is a frequent complication after PBSC haploidentical T‐repleted HSCT, but significantly less frequent after HLA‐identical HSCT. Most cases are mild. Prompt identification allows adequate management of severe forms.